Menas Adamancy vs. Womenas Fidelity: An Anthropological Analysis of Menas Perception Regarding Womenas Empowerment in Pakhtun Society (Global Journal of Human-Social Science, 2012)
The current study is an anthropological analysis of men's perception towards women's empowerment based on quantitative and qualitative approach. Chakdara town of District Dir (Lower), Khyber Pakhtunkhawa, Pakistan was ethnographically selected and a survey of 4564 households has been analyzed which was conducted during the PhD field study in 2008, where data was collected through semistructured interview schedule from a total of 100 respondents including religious scholars, educated males and females. Besides, the researchers have enumerated the issue under the extensive study pertaining relevant communal and global literature dealing with Pakhtun culture with a theoretical framework including Gender and Development Model and Women Empowerment Forum.
Keywords: perception; empowerment; patriarchy; pakhtunwali; gender; obstacles